Analisis Pengaruh Intention to Boycott & Brand Exposure terhadap Purchase Decision Melalui Brand Image pada Produk Scarlett Whitening di Kota Makassar - Andi Shinta Ria Oktaviani; Chalid Imran Musa; Nurul Fadilah Aswar; Zainal Ruma; Rahmat Riwayat Abadi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to determine the effect of Intention to Boycott and Brand Exposure on Purchase Decision mediated by Brand Image on Scarlett Whitening products in Makassar City. This research uses a quantitative approach with a causal design. The population in this study is the community of Makassar City who have used or are familiar with Scarlett Whitening products. The sample was taken using a non-probability sampling method with a purposive sampling approach, and 105 respondents were obtained. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) version 4.0. The results of the study show that (1) Intention to Boycott has a direct negative and significant effect on Brand Image, (2) Brand Exposure has a direct positive and significant effect on Brand Image, (3) Intention to Boycott has a direct negative and significant effect on Purchase Decision, (4) Brand Exposure has a direct positive and significant effect on Purchase Decision, (5) Brand Image has a direct positive and significant effect on Purchase Decision, (6) Brand Image significantly mediates the relationship between Intention to Boycott and Purchase Decision, and (7) Brand Image significantly mediates the relationship between Brand Exposure and Purchase Decision.